Lack of activation of UCP1 in isolated brown adipose tissue mitochondria by glucose-O-ω-modified saturated fatty acids of various chain lengths. - Porter, Richard (My University, 2013)
We previously demonstrated that uncoupling protein 1 activity, as measured in isolated brown adipose tissue mitochondria (and as a native protein reconstituted into liposome membranes), was not activated by the non-flippable modified saturated fatty acid, glucose-O-ω-palmitate, whereas activity was stimulated by palmitate alone (40 nM free final concentration). In this study, we investigated whether fatty acid chain length had any bearing on the ability of glucose-O-ω-fatty acids to activate uncoupling protein 1. Glucose-O-ω-saturated fatty acids of various chain lengths were synthesized and tested for their potential to activate GDP-inhibited uncoupling protein 1-dependent oxygen consumption in brown adipose tissue mitochondria, and the results were compared with equivalent non-modified fatty acid controls. Here we demonstrate that laurate (12C), palmitate (16C) and stearate (18C) could activate GDP-inhibited uncoupling protein 1-dependent oxygen consumption in brown adipose tissue mitochondria, whereas there was no activation with glucose-O-ω-laurate (12C), glucose-O-ω-palmitate (16C), glucose-O-ω-stearate (18C), glucose-O-ω-arachidate (20C) or arachidate alone. We conclude that non-flippable fatty acids cannot activate uncoupling protein 1 irrespective of chain length. Our data further undermine the cofactor activation model of uncoupling protein 1 function but are compatible with the model that uncoupling protein 1 functions by flipping long-chain fatty acid anions.
PUBLISHED
Keywords: UCP1; Mitochondria; Glucose-O-ω-fatty acids; BAT; Immunology, Inflammation & Infection; Biochemistry, metabolism